A6.05 Optimisation of the THP-1 cell model system for interrogation of differential macrophage polarisation in human disease. (24th February 2016) - Graham, AE; Re, NA; Baxter, E; Carr, I; Robinson, JR; Aslam, A; Antanaviciute, A; Mackie, SL; Morgan, AW
Abstract : Background and objectives: Macrophages are a heterogeneous population of cells that play a central role in the pathogenesis of multiple autoimmune and inflammatory disorders. In tissues, macrophages are activated by a diverse array of signals, adopt distinct phenotypes and undertake a wide range of effector functions. Mimicking the Th cell nomenclature, a M1/M2 model of macrophage polarisation was initially proposed in murine models and has been increasingly applied to human disease. THP-1 cells are commonly used in disease model systems, however, differentiation protocols vary widely e.g. concentration and exposure times of priming agent (PMA) and polarising cytokines, necessitating the need for standardisation. M1 protocols have dominated previous literature; possibly due to the absence of clear markers and subset definition for the anti-inflammatory, M2 subtype. Our aim is to identify novel transcriptional signatures that can be used for the interrogation of human disease and ultimately the development of disease-specific in vitro models. Materials and methods: Reported M1- and M2-specific macrophage markers were initially used as outcome measures of THP-1 polarisation experiments investigating transcriptional alterations in response to PMA concentration, rest period, cytokine stimulation times and concentrations. Publicly available RNA-seq datasets derived from human primary macrophage subtypes were used to identify additional markers. NOS and arginase production were measured to functionally confirm polarisation towards an M1 or M2 phenotype. Results: Optimal conditions were selected based on the upregulation of M1 (CXCL10, IL-6 and INHBA) or M2 (CD206, CCL17 and TGM2) transcripts. A low level of PMA (5 ng/ml) and an extended rest period (72 h) were found to be sufficient to induce macrophage maturation, whilst preventing M1 polarisation bias, prior to cytokine stimulation. Characterisation of novel markers identified through analysis of public RNA-seq data is underway, along with generation of RNA-seq data from our optimised conditions. Conclusions: We are developing a THP-1 cell model for generating pro- and anti-inflammatory macrophages that resemble populations found in disease states. Marker panels and transcriptional signatures will ultimately be applied to the investigation of macrophage phenotypes found in vivo .